2023
DOI: 10.1186/s12885-023-10747-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study on active surveillance after neoadjuvant chemoradiotherapy for esophageal cancer: protocol of Surgery As Needed for Oesophageal cancer-2

Abstract: Background Neoadjuvant chemoradiotherapy (nCRT) followed by esophagectomy is a standard treatment for potentially curable esophageal cancer. Active surveillance in patients with a clinically complete response (cCR) 12 weeks after nCRT is regarded as possible alternative to standard surgery. The aim of this study is to monitor the safety, adherence and effectiveness of active surveillance in patients outside a randomized trial. Methods This nationwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Multiple retrospective studies have demonstrated that among good responders after neoadjuvant therapy, active surveillance of patients who refused esophagectomy or were ultimately deemed unsuitable for surgery had comparable survival rates to those who underwent surgery ( 173 178 ). In the ongoing prospective SANO trial and ESOSTRATE trial, patients with a clinical response assessment of cCR after standard neoadjuvant chemoradiotherapy will be randomly assigned to either the active surveillance group or the immediate surgery group, comparing survival and quality of life for both groups ( 179 181 ). Neoadjuvant chemoradiotherapy combined with immunotherapy has achieved a pCR rate exceeding 50% potentially enabling more responders to bypass surgery, thereby retaining their esophageal function and improving survival with a higher quality of life.…”
Section: Discussion: Current Progress and Future Directionmentioning
confidence: 99%
“…Multiple retrospective studies have demonstrated that among good responders after neoadjuvant therapy, active surveillance of patients who refused esophagectomy or were ultimately deemed unsuitable for surgery had comparable survival rates to those who underwent surgery ( 173 178 ). In the ongoing prospective SANO trial and ESOSTRATE trial, patients with a clinical response assessment of cCR after standard neoadjuvant chemoradiotherapy will be randomly assigned to either the active surveillance group or the immediate surgery group, comparing survival and quality of life for both groups ( 179 181 ). Neoadjuvant chemoradiotherapy combined with immunotherapy has achieved a pCR rate exceeding 50% potentially enabling more responders to bypass surgery, thereby retaining their esophageal function and improving survival with a higher quality of life.…”
Section: Discussion: Current Progress and Future Directionmentioning
confidence: 99%
“…All patients underwent five weekly cycles of carboplatin/paclitaxel with concurrent 41.1 Gy of radiotherapy [1]. Patients were consecutively identified between February 2021 and May 2022 from the Surgery As Needed for Oesophageal Cancer (SANO)-2 study, an extension study of the SANO trial [10]. Exclusion criteria were contra-indications for MRI and an 18 F-FDG nonavid tumor at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…This study was performed in the context of the SANO-2 study, a multicenter prospective observational cohort study that monitors the safety and effectiveness of active surveillance while awaiting the results of the randomized trial. 3 The study was initiated by the Erasmus MC Cancer Institute and was conducted at 11 hospitals in The Netherlands. The study was approved by the Medical Ethical Committee of the Erasmus MC (MEC 2021-0068) and was registered at ClinicalTrials.gov (NCT04886635).…”
Section: Methodsmentioning
confidence: 99%
“…Operable patients above 18 years of age who underwent or were planned to undergo nCRT according to the CROSS regimen followed by surgical resection for histologically proven adenocarcinoma or squamous cell carcinoma of the esophagus or junction at the Erasmus MC Cancer Institute were offered DC. 3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation